Allergic contact dermatitis caused by dipropylene glycol diacrylate in the Omnipod® insulin pump. (2nd November 2021) - Ulriksdotter, J.; Svedman, C.; Bruze, M.; Mowitz, M.
Summary: Background: Cases of allergic contact dermatitis (ACD) caused by isobornyl acrylate (IBOA) in the Omnipod® insulin pump have previously been reported. Objectives: To present three cases of patients with ACD caused by a new allergen in the pump, and results from chemical analyses. Methods: Omnipod pumps from different batches were analysed by gas chromatography–mass spectrometry. Aimed testing, with the department's medical device (MD) series and substances identified in the pump including dipropylene glycol diacrylate (DPGDA) at 0·01% and 0·1% in petrolatum (pet.), was performed. Patch testing also included extracts from the device, the adhesive patch as is, and allergens from baseline series. Results: All patients tested positive to 0·1% DPGDA in pet., and two patients additionally to a 0·01% concentration. DPGDA was found in extracts of the Omnipod pumps brought by the patients. An Omnipod pump from an earlier batch contained tripropylene glycol diacrylate, IBOA, N, N ‐dimethylacrylamide, di(ethylene glycol)ethyl ether acrylate (DEGEA) but no DPGDA. One of the patients reacted positively to all of these allergens except DEGEA, which was not tested. Conclusions: When suspecting ACD to MDs, DPGDA at 0·1% in pet. should be tested. The contents of Omnipod have changed over time. Patch testing with updated test series and relevance assessment of positive reactions is a delicate task. Children, with lifelong use of MDs, risk contracting many allergies with potential cross‐allergies. A question should be raised as to whether these low molecular weight acrylates should be used at all in devices constantly worn on the skin. Abstract : What is already known about this topic? Contact allergy to medical devices (MDs) is a growing clinical problem. Isobornyl acrylate is a culprit allergen found in several different MDs in recent years. What does this study add? Dipropylene glycol diacrylate has now for the first time been identified in an MD. There is evidence of alteration in device contents between batches, risking polysensitization among users. Linked Comment:  T. Agner and A. Goossens. Br J Dermatol 2022; 186:212–213 . Plain language summary available online